The Effectiveness of Hospital Management on Increasing Productivity of Nurse Performance in Hospitals Royal Prima, Medan - M.Rizki Fadirah Harahap; Ermi Girsang; Santy Deasy Siregar (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
This study aims to evaluate the effectiveness of hospital management in increasing the productivity of nurse performance at Royal Prima Hospital, Medan. This study uses a quantitative approach with a cross-sectional design, which was conducted at Royal Prima Hospital in 2024. The study population was 60 nurses working in the hospital, with a sample of 60 nurses selected using a random sampling technique. Inclusion criteria include nurses who have more than one year of work experience, are willing to be respondents, and are not on leave or in further education. The research instrument is in the form of a questionnaire that covers aspects of hospital management and nurse performance productivity. The data was analyzed using the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) approach using SmartPLS version 3.0. The results of the t-test showed that the effectiveness of hospital management had a significant positive influence on nurse productivity (t count = 3.981 > t table = 2.001; p-value = 0.000). The F test shows a significant model with a calculated F value of 12.34 (F table = 3.15). In the early stages of the analysis, the valid indicators were the effectiveness of management communication (X.2) and the level of patient satisfaction (Y.2), with an outer loading > of 0.7. After the removal of invalid indicators, all variables met convergent validity (AVE > 0.5) and reliability (Cronbach Alpha > 0.7). The results of the study emphasize the importance of effective communication and coordination between management and nursing staff to create a work environment that supports increased productivity. Hospitals are advised to improve communication-related training, strengthen cross-departmental coordination, and adopt data-driven management policies to support strategic decision-making. These findings are expected to strengthen the quality of health services and increase patient satisfaction. Keywords: Communication, Effectivenes, Hospital,Management, Nurse Productivity